Environmental social responsibility, local environmental protection strategy, and corporate financial performance: Empirical evidence from heavy pollution industry - Changlin Ji; Yuwei Feng; Xingnan Guo (Economics: The Open-Access, Open-Assessment Journal, 2024)
This article empirically examines the "responsibility-performance" interaction in the process of environmental social responsibility decision-making by enterprises, using the listed companies in the heavy pollution industry as the research sample. We also use the evolutionary game theory to construct a system dynamics model for simulation analysis to explore the evolutionary qualities of the environmental responsibility behavior of heavily polluting enterprises and its relationship with financial performance under the influence of local government environmental regulation. It finds that for environmental social responsibility, a company's expected performance surplus is more likely to promote positive interaction between responsibility and performance than a gap; for regions with relatively negative environmental strategies, environmental social responsibility provides more efficient reputation transformation and motivates companies to invest in it; more competitive industries and enterprises with forward-looking environmental strategies tend to put performance feedback into the undertaking of environmental social responsibility. Therefore, the government and regulatory authorities should urge heavy polluting enterprises to implement environmental responsibility, so that they can fully realize that emission reduction and growth can be achieved at the same time and promote the financial performance of enterprises and environmental responsibility while forming a win-win situation at the ecological level and corporate social level.
Keywords: 330; environmental social responsibility; expected performance feedback; local environmental protection strategy; enterprise financial performance